LINGUISTIC SPECIFICATION OF MERONYMY IN ENGLISH AND UZBEK LANGUAGES - Ramazonov Jasur Jalil o'g'li, (TADQIQOTLAR, 2025)
Abstract: Meronymy, a semantic relation in which one lexical unit denotes a part, component, or member of a larger whole, plays a crucial role in lexical semantics and cognitive linguistics. This article investigates the linguistic specification of meronymy in the English and Uzbek languages, examining its structural, semantic, and functional properties. Using descriptive, contrastive, and analytical methods, the study analyzes meronymic relations in authentic texts, dictionaries, and corpora, focusing on how part-whole relationships are expressed and conceptualized in each language. The analysis reveals that English and Uzbek share universal cognitive principles in organizing part-whole  relations,  but  they  differ  significantly  in  linguistic  expression  and  cultural representation. English often encodes meronymy through concise nominal compounds and prepositional constructions (wheel of a car, branch of a company), whereas Uzbek utilizes  morphologically  marked,  explicit  descriptive  structures  (mashinaning g‘ildiragi,  kompaniyaning  bo‘limi).  These  differences  reflect  both  typological distinctions and culturally influenced conceptualizations of part-whole relationships. Furthermore,  the  study  highlights  challenges  in  translation  and  cross-linguistic interpretation  of  meronymic  relations,  emphasizing  the  importance  of  semantic, syntactic, and pragmatic awareness.